2008
DOI: 10.1007/s11524-008-9319-2
|View full text |Cite
|
Sign up to set email alerts
|

Social Patterning of Chronic Disease Risk Factors in a Latin American City

Abstract: Most studies of socioeconomic status (SES) and chronic disease risk factors have been conducted in high-income countries, and most show inverse social gradients. Few studies examine these patterns in lower- or middle-income countries. Using cross-sectional data from a 2005 national risk factor survey in Argentina (a middle-income country), we investigated the associations of individual- and area-level SES with chronic disease risk factors (body mass index [BMI], hypertension, and diabetes) among residents of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
54
3
11

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 44 publications
7
54
3
11
Order By: Relevance
“…Rev BRas epidemiol JaN-maR 2017; 20(1): [16][17][18][19][20][21][22][23][24][25][26][27][28][29] Commonly, diabetes seems to be associated with other conditions, such as arterial hypertension and dyslipidemia, which corroborates the findings of this study. In the city of Campos, Rio de Janeiro, it was observed that individuals with hypertension or dislipedimia showed three times more of a chance of having DM when compared to the population unexposed to these factors 11 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Rev BRas epidemiol JaN-maR 2017; 20(1): [16][17][18][19][20][21][22][23][24][25][26][27][28][29] Commonly, diabetes seems to be associated with other conditions, such as arterial hypertension and dyslipidemia, which corroborates the findings of this study. In the city of Campos, Rio de Janeiro, it was observed that individuals with hypertension or dislipedimia showed three times more of a chance of having DM when compared to the population unexposed to these factors 11 .…”
Section: Discussionsupporting
confidence: 87%
“…Such association had already been verified previously, in Brazil and other countries 13,19,20 . The prevalence of diabetes found in a Brazilian region marked by low income and low levels of education Rev BRas epidemiol JaN-maR 2017; 20 (1): [16][17][18][19][20][21][22][23][24][25][26][27][28][29] demonstrated to be much higher than among adults in other regions 12 . Education level demonstrated to be an important socioeconomic indicator, as it is considered a proxy of the social position of an individual.…”
Section: Discussionsupporting
confidence: 77%
“…In considering the second explanation, it is important to note that, in recent years, the association between urbanicity, smoking, and lung cancer mortality seems to have become less pronounced for males (Schouten et al 1996;Fleischer 2010). Also, in our study we found less evidence for a role of urbanicity among males than among females.…”
Section: Sex Differences In the Contribution Of Smoking And In Regioncontrasting
confidence: 68%
“…The first explanation can be related to the general observed trend in social gradients in chronic disease risk factors (Fleischer 2010): that is, people with higher socio-economic status (SES) tend to adopt new lifestyles first, while people with lower SES tend to take up these lifestyles later, but then generally have more difficulty quitting (e.g., Fleischer 2010). This trend has indeed been observed for smoking (e.g., Kunst, Looman, and Mackenbach 1993).…”
Section: Sex Differences In the Contribution Of Smoking And In Regionmentioning
confidence: 99%
“…Moreover, official classification based on WHO criterion shows that obesity and overweight are real problems requiring to be tackled urgently, but in the meanwhile proper definitions have to be developed in these countries in order to set up appropriately targeted intervention programs in the future [18,19].…”
Section: Discussionmentioning
confidence: 99%